2017
DOI: 10.4038/sljch.v46i4.8382
|View full text |Cite
|
Sign up to set email alerts
|

A prospective observational study of retinopathy of prematurity in a tertiary care centre with respect to its incidence, risk factors and short term outcomes

Abstract: Introduction: Retinopathy of prematurity (ROP) is an important cause of blindness in children. Early detection and timely intervention decreases the morbidity associated with it.Objectives: To determine the incidence, risk factors and short term outcomes of ROP in a tertiary care centre and compare it to unpublished data from the same centre from 2010-2012.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…In our study, the prevalence of retinopathy of prematurity was 17 (28%). This was in concurrence with study by Manohar et al, 13 conducted at Pune, where the incidence was 19.9% and study by Gupta et al, 14 of 60 babies, found incidence of ROP at 21.7%. In a study done by Anudeep et al, out of the 65 preterm babies screened, 24 (37%) developed ROP.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the prevalence of retinopathy of prematurity was 17 (28%). This was in concurrence with study by Manohar et al, 13 conducted at Pune, where the incidence was 19.9% and study by Gupta et al, 14 of 60 babies, found incidence of ROP at 21.7%. In a study done by Anudeep et al, out of the 65 preterm babies screened, 24 (37%) developed ROP.…”
Section: Discussionsupporting
confidence: 90%